Motivating students using Project Based Learning (PjBL) via e-SOLMS technology - Jusoff, Kamaruzaman; Abdul Rahman, Baharuddin; Mat Daud, Khairul Azhar; Abd Ghani, Nik Azida (IDOSI Publications, 2010)
This paper focuses on PjBL concept via online learning instrument, Student Oriented Learning Management System (e-SOLMS). The PjBL module is supported with “ online” web-based system called e-SOLMS. This system has been pilot tested on Mechanical Engineering students at Kota Bharu Polytechnic, Kelantan, Malaysia. It is hoped that this PjBL: eSOLMS becomes as alternative of new online learning resource for technical and vocational education in Malaysia. This system enables continuous monitoring of the students’ project development progress by lecturers or supervisors and parents. This study finds that engineering students who are attached with PjBL:eSOLMS demonstrate increases in their intrinsic orientation.